Determinants of Mentoring in the Context of Human Capital Development. Modeling the Effectiveness of the Mentoring Processes in Business Tourism Organization - BARAN, Małgorzata (Journal of Environmental Management and Tourism, 2022)
The aim of the study was to examine the determinants of the mentoring processes from the perspective of HR managers from companies in different branch of the tourism industry and the impact of these conditions on the effects of mentoring related to human capital development. The characteristics of mentoring’ determinants were singled out in order to build a model of mentoring effectiveness which could be applied for increase the quality of HR in tourism activities. A group of four hypotheses were formulated on the basis of the identified cognitive gaps. A qualitative study was conducted with the use of triangulation procedure. The study indicates that the organizational, motivational, and relational determinants as well as the determinants related to HRM have a significant impact on the level of the effects of mentoring related to employee development in companies. The statistically significant interactions were obtained between the number of meetings per edition within the mentoring process and the level of institutional and relational determinants, and between the length of mentoring used in the company and the level of determinants related to human resource management and motivational determinants.